OCCUPATIONAL STRESS, QUALITY OF LIFE AND CARING BEHAVIOUR AMONG INDONESIAN NURSES IN JAPAN - Nununk Dwi Nur Khairunnissa; Ferry Efendi; Erna Dwi Wahyuni; Rifky Octavia Pradipta; Andi Safutra Suraya; Yong Shian Goh (Universitas Airlangga, 2026)
Background: Japan recruits Indonesian nurses to address shortages, but migrant nurses’ work stress may reduce their quality of life and caring behavior Aims: This study analyzed links between occupational stress, quality of life, and caring behavior among Indonesian nurses working in Japan, using the Health and Safety Executive (HSE) work-related stress scale, World Health Organization Quality of Life (WHOQOL-BREF), and Caring Behaviors Inventory (CBI-24). Methods: A correlational cross-sectional study with purposive sampling involved 138 Indonesian nurses in Japan. Data were collected via Google Forms using the HSE Work-Related Stress Scale, WHOQOL-BREF, and CBI-24. Pearson’s correlation test (α ≤ 0.05) was applied to analyze relationships among occupational stress, quality of life, and caring behavior. Results: Job stress correlated with quality of life (p = 0.000; r = 0.595) and caring behavior (p = 0.000; r = 0.411) among Indonesian nurses in Japan. Conclusion: Work-related stress was significantly linked to QoL and caring behavior. Despite moderate stress, most nurses maintained good QoL and optimal caring, reflecting resilience in cross-cultural healthcare. Findings highlight the need for effective workforce management and leadership to sustain care quality. These results offer evidence-based insights for strengthening health systems, particularly in governance and policy planning for transnational nurse deployment. Keywords: caring behavior, decent work, job stress, migrant nurses, quality of life.